Diferença salarial entre gêneros: análise das regiões brasileiras os anos de 2016 a 2021 - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
The objective of this research is to analyze the wage gap between genders in Brazilian macro-regions. To this end, a theoretical framework was sought on the concepts of human capital, segmentation in the labor market and discrimination, including reports on factors that generate salary differentials. Some authors used are Schultz (1964, 1973), Becker (1957, 1973), Mincer (1958), Doeringer and Piore (1970), who demonstrate that human capital is one of the main sources that can contribute to increasing the level of income. A data search was carried out with analysis of microdata from the Continuous PNAD, with data from large Brazilian regions in the period from 2016 to 2019, and the years 2020 and 2021 with the influence of Covid-19, for female and male individuals. The method used to analyze the data was the confidence method of Oaxaca-Blinder (1973), which makes an economy of the average income of each gender, where the differences are divided into a part explained by the productive differences of individuals and another not explained. explained, with questions such as color, race, gender, religion. The results show that men have lower levels of education and higher income compared to women. The divergence becomes noticeable when the data is analyzed by region, as it is found that more economically developed regions have higher rates of discrimination and inequality than regions with lower average salaries. Therefore, through the reduction in income we can find the persistence of discrimination between genders. It was also possible to verify that there was an increase in the discriminatory size in the Northeast and North regions in the years 2020 and 2021, periods affected by Covid-19, where salary levels in previous years did not have an upward trend.
Keywords: Diferenciais salariais; Gênero; Discriminação; Salary differentials; Gender; Discrimation; CNPQ::CIENCIAS SOCIAIS APLICADAS::ECONOMIA